(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
هدف البحث الحالي إلى رسم ملامح أولية لفلسفة إسلامية في التربية في مسائل الوجود والقيم والمعرفة استناداً إلى ما ورد في القرآن والسنة وأقوال السلف الصالح بهدف تعليم الأجيال المسلمة طرقاً متجددة للحياة والتفكير والتكيف مع المستجدات وبناء علاقة قوية بينه وبين أخيه الإنسان. ولذلك استخدم البحث المنهج الوصفي التحليلي وخاصة تحليل مضمون النصوص الإسلامية في مجالات الوجود والقيم والمعرفة المذكورة أعلاه. وقد بيّن البحث نظرة الإسلام للوجود والإنسان والحياة وبيّن رؤية الإسلام لطبيعة الإنسان ومبادئها وإلى الوجود ومعالمه وإلى الحياة وجوانبها المختلفة. كما قدّم البحث ملامح أولية لنظرية القيم في الإسلام موضحاً معناها وأهميتها وخصائصها وتصنيفها كقيم التقوى والكفر والنفاق سواء كانت قيم خلقية أو روحية أو علمية أو اجتماعية أو جمالية. وبيّن البحث المشكلات التي تواجهها القيم الإسلامية وخاصة تلك التي جاءت من الخارج أو من النظريات الأخرى أو من الصراع بين نظم القيم الإسلامية ذاتها وفي تقديم نظرية المعرفة في الإسلام ثم توضيح مفهومها وغايتها وأهميتها وشروطها الطبيعية اليقينية والنفعية وخطواتها ومصدرها ومبادئها وأدواتها ونماذجها. وأخيراً ناقش البحث علاقة الوجود والقيم والمعرفة بالنظام التربوي مركّزاً بشكل واضح على تربية الإنسان المسلم وتربية عقله على الاجتهاد وحرية التفكير والاعتراض مع احترام الضرورات الخمس والالتزام بها.. The aim of this research is to shape the initial prospects of Islamic philosophy in education in matters of existence, values, ​​and knowledge on the basis of the Qur’an and Sunnah and the statements of Ancestors to introduce Muslim generations to new ways of life, thinking, adapting to new developments and building a strong relationship among human beings. Therefore, the researcher uses the descriptive analytical method, especially the content analysis of Islamic texts in the areas of existence, values, ​​and knowledge. To look into the Islamic view of life and human life and the vision of Islam on human nature, principles, and existence and its features and life and its different aspects, the researcher presents the features of an initial theory of values ​​in Islam, explaining its meaning, significance, characteristics, and classification of the values ​​of piety, blasphemy, and hypocrisy, be they moral, spiritual, scientific, social, or aesthetic. The research highlights the problems facing Islamic values, especially those coming from overseas or from other theories or from the conflicting systems of Islamic values ​​themselves and the theory of knowledge in Islam, clarifying its concept and significance. Finally, this study discusses relationship of existence, values, ​​and knowledge with the educational system, focusing on elevating the Muslim mind in terms of hard work, freedom of thought, and the right to object.